2D and 3D graphene nanocomposites fundamentals, design, and devices - Glukhova, Olga (Singapore : Jenny Stanford Publishing, 2019)
In recent decades, graphene composites have received considerable attention due to their unique structural features and extraordinary properties. 2D and 3D graphene hybrid structuresare widely used in memory,microelectronic, and optoelectronic devices; energy- and power-density supercapacitors; light-emitting diodes; andsensors, batteries, andsolar cells. This book covers the fundamental properties of the latest graphene-based 2D and 3D composite materials. The book is a result of the collective work of many highly qualified specialists in the field of experimental and theoretical research on graphene and its derivatives. It describes experimental methods for obtaining and characterizing samples of chemically modified graphene, details conceptual foundations of popular methods for computer modeling of graphene nanostructures, and compiles original computational techniques developed by the chapter authors. It discusses the potential application areas and modifications of graphene-based 2D and 3D composite materials and interprets the interesting physical effects discovered for the first time for graphene materials under consideration. The book is useful for graduate students and researchers as well as specialists in industrial engineering. It will also appeal to those involved in materials science, condensed matter physics, nanotechnology, physical electronics, nano- and optoelectronics.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Nanostructures; SCIENCE / Physics; SCIENCE / Life Sciences / General; Nanocomposites (Materials); Graphene